Pengaruh Kinerja Kepala Sekolah dan Kompetensi Profesionalisme Guru terhadap Prestasi Siswa di SMK Kesehatan Annisa 3 Citeureup Bogor - Deni Rahayu; Imam Tolkhah; Mohamad Jaenudin (LPPM Institut Nasional Laa Roiba Bogor, 2020)
The purpose of this study was to determine the effect of Principal Performance on Student achievement, the effect of Teacher Professionalism Competence on Student Achievement, and the joint effect of Principal Performance and Teacher Professionalism Competence on Student Achievement at SMK Annisa 3, Citeureup, Bogor. This research is a survey research with a quantitative approach. Survey research is intended to obtain a general description of the research variables. To explain the research variables carried out with a descriptive and correlative level of explanation. Descriptive explanatory level aims to describe the findings of variables from the study. While the correlative level of explanation is used to find relationships between variables. The results of the study showed that (1) There was a significant positive effect on the Principal's Performance on student achievement in Health Vocational School Annisa 3, Citeureup, Bogor. The Principal's performance contributes highly to student achievement at SMK Annisa 3 Health, Citeureup, Bogor. as much as 54.8%. (2) There is a significant positive effect on Teacher Professional Competence on Student Achievement in Annisa 3 Health Vocational School, Citeureup, Bogor. Professional Teacher Competence contributes highly to Student achievement at Annisa 3 Health Vocational School, Citeureup, Bogor as much as 78.4%. (3) There is a positive influence that is significantly shared by School Principal Performance and Teacher Professional Competence on Student Achievement in Health Vocational School Annisa 3, Citeureup, Bogor. Correlation between the principal's performance, teacher's professional competence and student achievement is strong. R Square value of 0.332 or 33.2% indicates that there is an influence of independent variables (principal performance, teacher professional competence) on the dependent variable (student achievement) of 33.2% which can be explained by research factors, while 66,8% or (1-33.2%) are explained by other factors outside of research.